Blockade of the cholinergic system during sensitization enhances lung responsiveness to allergen in rats. (6th August 2018) - Malaspinas, Iliona; Petak, Ferenc; Baudat, Aurélie; Doras, Camille; Eigenmann, Philippe A.; Habre, Walid
Summary: Although acute prophylactic administration of atropine modulates airway responsiveness, the role of the parasympathetic nervous system in the pathogenesis of sensitization and in antigen‐induced bronchoconstriction remains unclear. The aim of the present study is to determine whether blocking muscarinic receptors during chronic allergen exposure modulates lung responsiveness to the specific allergen. Forty rats were randomly assigned to one of the following five treatment groups: sensitization with saline vehicle, intraperitoneal injection of ovalbumin (1 mg) with or without atropine treatment (10 mg/kg per day) and repeated ovalbumin aerosol (1.25 mg/mL for 20 minutes) either alone or combined with atropine. Lung responsiveness to methacholine (4–16 μg/kg per minute) and intravenous ovalbumin (2 mg) was established before and 21 days after treatment with forced oscillations following bilateral vagotomy. Lung cellularity was determined by analysis of bronchoalveolar lavage fluid (BALF). A lung inflammatory response in all sensitized animals was defined as an increase in the number of inflammatory cells in the BALF. Baseline respiratory mechanics and methacholine responsiveness on Days 0 and 21 were comparable in all groups. However, increases in airway resistance following intravenous allergen challenge were significantly exacerbated in rats that received atropine. Inhibition of the cholinergic nervous system during allergic sensitization potentiates bronchoconstriction following exposure to the specific allergen. These findings highlight the role of the cholinergic neuronal pathway in airway sensitization to a specific allergen.